Cell phone support to improve medication adherence among solid organ transplant recipients. (19th June 2018) - Sayegh, Caitlin S.; Szmuszkovicz, Jacqueline R.; Menteer, Jondavid; Sherer, Sara; Thomas, Daniel; Lestz, Rachel; Belzer, Marvin
Abstract: For many adolescent and young adult solid organ transplant recipients, medication non‐adherence is a mortal issue. This study investigated the feasibility, acceptability, and potential efficacy of a 12‐week cell phone support intervention to improve immunosuppressant medication adherence. A small sample ( N = 8) of non‐adherent adolescent and young adult transplant recipients, aged 15‐20.5 years, was enrolled. Cell phone support consisted of short calls each weekday including medication reminders, discussion of needs, problem‐solving support, and promotion of clinic and community resources. Changes in adherence were measured by self‐report and laboratory values, and intervention acceptability, adherence barriers, social support, depression, and substance use were assessed by self‐report. Pre‐post effect sizes showed medium‐to‐large improvements in adherence, lasting through a 12‐week follow‐up assessment. There were also small‐to‐medium changes in adherence barriers, social support, and depression. However, acceptability and feasibility were limited, due to a low rate of enrollment by eligible male participants. Cell phone support interventions may promote medication adherence among adolescents and young adults. Cell phone support warrants further investigation, including a randomized controlled trial to evaluate efficacy.